LINGUOPRAGMATIC FEATURES OF THE CONCEPTS OF “LONELINESS” “(YOLG’IZLIK)” AND «PARTING” (HIJRON) IN UZBEK AND ENGLISH LITERARY TEXTS (TAMADDUN NURI JURNALI, 2025)
Considering the problem of experiencing loneliness, it is worth noting the following: with regard to the emotional component of the experience of loneliness, the mechanism of its realization is the reflection, understanding and subsequent embodiment of this experience in conceptual units. This article is dedicated to the linguopragmatic features of the concepts of “loneliness” and “parting” in uzbek and english literary texts.